The Impact Of Leadership Style and Work Environment On Employee Performance: Case Study At PT. Warna Warni Investama Surabaya - Achmad Daengs Gs; Enny Istanti; Rina Dewi; Diana Zuhro; Indriana Kritiawati (International Journal of Economics, Commerce, and Management, 2024)
The purpose of this research is to determine: (1) The partial influence of leadership style and work environment on employee performance at PT. Color Warni Investama with an Fcount value of 57.061 in Sig. (P) = 0.000. or Fcount > Ftable (57.061 > 3.14); (2) To determine the influence of leadership style and work environment simultaneously on employee performance at PT. Colorful Investama; (3) The leadership style variable is the dominant variable that influences employee performance. The sample used in this research was 65 people. In this research, data analysis uses multiple linear regression statistics with the help of the SPSS program. The results of the research show that: (1) leadership style and work environment variables simultaneously have a significant effect on employee performance, (2) leadership style and work environment variables partially have a significant effect on employee performance, (2) leadership style variables have a significant effect on employee performance with a tcount value of 6.346 in Sig. (P) = 0.001 or tcount > ttable (6.3469>1.998); (3) that work environment variables have a significant effect on employee performance; (4) The leadership style variable is the dominant variable that influences employee performance. This can be seen from the standard leadership style beta coefficient of 0.551 > the work environment beta coefficient of 0.374.